Upaya Penanggulangan Tindak Pidana Korupsi di Indonesia - Fathur Rachman (KEADILAN PROGRESIF, 2018)
Corruption cannot be formulated in just one sentence which might be to make a reasonable picture of these symptoms so that we can separate them from other symptoms that are not corruption. The essence of corruption is the misuse of trust for personal interests. Brooks's formulation of corruption is "intentionally making mistakes or neglecting tasks that are known as obligations, or without the right to use power, with the aim of obtaining a little profit for him". the law that will be reviewed is related to what is the cause of corruption, and how to overcome it. Settlement of these problems by reviewing the regulatory provisions that apply in Indonesia. Corruption occurs due to abuse of authority and position held by officials or employees for personal interests in the name of personal or family, relatives and friends. One attempt to eradicate corruption is to give rights to community to get access to information. Need to establish a system where the community (including the media) is given the right to request all information relating to government policies that are related to the lives of many people.